Az „egyházi év” fogalmának eredete - PAP, Ferenc (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2016)
Origin of the term „church year” This study deals with the origins, roots and theological meaning of the liturgical year. Terms used in various languages (Latin, English, German and Hungarian) for liturgical year in the history of the church are gathered and listed in this presentation. The term “church year” (German: Kirchenjahr) appeared first in the Apostil, which consists of sermons for the annual cycle, written and published in 1585 and in 1587 by Johann Pomarius the Younger (originally: Baumgart; Pomarius is the Latinised form of the name), Lutheran Pastor in Magdeburg. “Church year” is a Protestant reflection on the Tridentine liturgical reform and on the changes of the calendar by the Pope Gregory XIII. Since1585–1587, the first Sunday of Advent marks the beginning of the new Christian year, which is called “church year”. Advent has become the opening of the new season of the liturgical year, but the very beginning of the “Christian year” has remained Christmas for centuries. Church year, Christian year and later on the secular interpretation of the year were divided into separate phenomena. The rediscovery of the tradition of the church year, bearing and interpreting the message of the Christian faith, could contribute to the renewal of our….. (hiányzik egy szó vagy kifejezés).